Edukasi Mitigasi Bencana Banjir dan Gempa Bumi pada Siswa Sekolah Dasar - Fida Husain; Ida Nur Imamah; Nining Puji Astuti; Nur Tjahjono Suharto; Asri Kusumastuti; Monica Inovasi; Indriana Astuti (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: Creating a program to establish a Disaster Safe Education Unit [Satuan Pendidikan Aman Bencana (SPAB)] is one of the initiatives the government is doing to prevent catastrophes and manage their effects in educational settings. Objective: The purpose of this community service project is to improve students' understanding of and proficiency in disaster preparedness. Method: The three types of activity approaches include planning, carrying out, and reviewing. 43 students participated in this activity, which involved a lecture and Q&A session. Result: It may be inferred from the activity's outcomes that educating students can help them become more knowledgeable about earthquake and flood disasters. The instructive exercise proceeded without any difficulties, and the participants engaged with great enthusiasm. Conclusion: In order to make sure that every student is aware of disaster readiness and can lower their risk of disaster, it is desired that the school would keep up its ongoing disaster preparedness education programs.